Analisis Semiotika pada Film Mat Kilau : Kebangkita Pahlawan - Harahap, Tamliha; Nursapia Harahap (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The many forms of communication media technology are advancing at an increasing rate in the contemporary globalization period. Global society has been significantly impacted by this. The mass media's emergence, which allows people to instantaneously communicate and enjoy content, is among the most significant achievements. Film is one of the products of mass media. A lot of movies are produced to impart life lessons, such the heroic and religious ideals of historical heroes, in an effort to instill in the millennial age a growing love for their nation and its religion, whatever form it may take. The selected item for this research was the movie Mat Kilau: Awakening of a Hero. The film's portrayal of the da'wah as well as the definitions of denotation, connotation, and myth present issues. Roland Barthes' semiotic analysis model is employed in this study. The study's findings demonstrate that the movie Mat Kilau conveys the Malay people's values of bravery and hardship in keeping with Islamic teachings. It also incorporates values of preaching through the actors' conversation.